Mainstreaming the Conservation Agriculture in Nepal (Journal of Agriculture and Environment, 2021)
Conservation agriculture (CA) system involves minimum soil disturbance, permanent soil cover, and crop rotations. In Nepal, efforts to develop, refine and disseminate conservation-based agricultural technologies started since the rice-wheat consortium in Terai in the 1990s. There are more payoffs than tradeoffs for the adoption of CA. Nepal Agricultural Research Council (NARC) with CIMMYT and IRRI has been working on it under various ecologies. Studies revealed that it reduces the production cost, saves water and nutrients, increases yields, improves soil health, mitigates global warming and improves resource use efficiency. However, there are many bottlenecks for its promotion; like lack of appropriate CA machineries, trade-offs of using crop residue in crop-livestock systems, crop residue burnings, unavailability of skilled manpower and peoples’ mindset. Therefore, there is an urgent need to develop strategies to mainstream the CA in Nepal. The paper highlights on strengths, weaknesses, opportunities, and threats of CA for promotion and the way forward.